2018
DOI: 10.5507/bp.2017.053
|View full text |Cite
|
Sign up to set email alerts
|

The presence of gasping predicts long-term survival in out-of-hospital cardiac arrest patients

Abstract: Background. The presence of gasping in out-of-hospital cardiac arrest (OHCA) patients predicts short-term prognosis. We performed a retrospective study to evaluate whether the presence of gasping at the time of Emergency Medical Service (EMS) arrival in the case OHCA patients of presumed cardian origin has any impact on six-month survival and/ or sustained return of spontaneous circulation (ROSC). Methods. We collected and analyzed Utstein Style data for all patients resuscitated for OHCA of presumed cardiac o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The remaining 26 full-text articles were assessed for eligibility, and 21 were excluded for various reasons (i.e., animal studies or different study content or populations). Finally, 5 studies [7, 1114] were included in the meta-analysis. The selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 26 full-text articles were assessed for eligibility, and 21 were excluded for various reasons (i.e., animal studies or different study content or populations). Finally, 5 studies [7, 1114] were included in the meta-analysis. The selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Martens et al reported two databases [12]. All five studies (six cohorts) reported the result of ROSC, two studies [13, 14] reported favorable neurological outcome at discharge or at 30 days after CA, two studies [11, 14] reported long term survival, four studies [7, 11, 13, 14] reported initial shockable rhythm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 A systematic review investigated whether agonal breathing predicts short-term and long-term outcomes in OHCA. 7 The review, which included five studies, showed that agonal breathing was associated with a significant increase in the rate of return of spontaneous circulation (risk ratio [RR], 1.87; 95% CI, 1.64–2.13) and with a higher likelihood of favorable neurological outcomes (RR, 3.79; 95% CI, 1.86–7.73) and increased long-term survival (≥6 months) (RR, 3.46; 95% CI, 1.70–7.07) 6 , 16 , 17 , 18 . Debaty G. 2017 et al, reported that the combination of agonal breathing and appropriate initial shock waveform for electrical shock application had higher for favorable patient outcomes compared to no agonal breathing and no shockable rhythm.…”
Section: Discussionmentioning
confidence: 99%